2016
DOI: 10.3389/fmicb.2016.01983
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Antibiotic Resistance Problem with Probiotics: Reducing the Risk of Its Double-Edged Sword Effect

Abstract: Antibiotic resistance is a global public health problem that requires our attention. Indiscriminate antibiotic use is a major contributor in the introduction of selective pressures in our natural environments that have significantly contributed in the rapid emergence of antibiotic-resistant microbial strains. The use of probiotics in lieu of antibiotic therapy to address certain health conditions in both animals and humans may alleviate these antibiotic-mediated selective pressures. Probiotic use is defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
136
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(154 citation statements)
references
References 82 publications
(282 reference statements)
0
136
0
4
Order By: Relevance
“…Bacteriocins are proteinaceous toxins produced by a wide range of bacteria and archaea and have a number of properties similar to antimicrobials that make them ideal candidates for pathogen control: potency, mode of action, target cells receptors, size, and structure [119]. Although their high selectivity make bacteriocins attractive alternatives to classical antibiotics, initial studies indicate that bacteriocinogenic bacteria may harbour AMR genes [119].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriocins are proteinaceous toxins produced by a wide range of bacteria and archaea and have a number of properties similar to antimicrobials that make them ideal candidates for pathogen control: potency, mode of action, target cells receptors, size, and structure [119]. Although their high selectivity make bacteriocins attractive alternatives to classical antibiotics, initial studies indicate that bacteriocinogenic bacteria may harbour AMR genes [119].…”
Section: Introductionmentioning
confidence: 99%
“…controls (Gu, Wei, & Yin, 2012;Wang et al, 2013). However, little is known about a number of critical issues in this context, such as the possible impact of probiotics on the normal microbiological flora (Imperial & Ibana, 2016), and the effects of administered drugs on the antibiotic susceptibility of probiotics. Some experimental animal data support the suggestion that antibiotic resistance genes are transferred to probiotic strains (Mater, Langella, Gérard Corthier, & Flores, 2008), although this aspect has not been studied in the hospital environment.…”
mentioning
confidence: 99%
“…Probiotics are considered as safe and viable alternatives for the health management for improved production in aquaculture (Martinez et al, 2012). Recent studies have shown the presence of genes that confer antibiotic resistance thereby posing a danger of transmission of such genes to pathogenic bacteria through horizontal gene transfer (Imperial et al, 2016). Tetracycline resistant genes viz., tetK, tetL tet M, tetO associated with tetracycline resistance have been reported in bacterial isolates.…”
Section: Resultsmentioning
confidence: 99%